The competence building in healthcare manager training - V. A. Reshetnikov; N. G. Korshever; A. I. Dorovskaya (Сеченовский вестник)
This article discusses the importance  of competence building in managerial health care staﬀ, and the development of appropriate competence building models (competence proﬁles). The authors did expert interviews of 16 professors of the organizational departments at Razumovsky Saratov State Medical University. We determined importance of the competencies presented in the State educational standard for «Health care organization and public health» programs for the department heads; deputy heads (vice-head) and head physicians (chiefs) of medical organizations, as well as what future graduates need «to know», «be able to» and «to have», i.e. formulated appropriate competence building models. These models can be used both to develop training programs and healthcare personnel policy.